Psychographic Segmentation of Facebook Users: A Cluster Analysis - Franklin John, S.; Senith, S.; Jino Ramson, S. R. (Indian Journal of Marketing, 2014)
Purpose: The aim of the study was to identify the usage pattern and purpose of using Facebook by individuals and to investigate the intentions of these segments to discuss brands during their daily social media communications. Design /Methodology/Approach: This study is a combination of both qualitative and quantitative approach. The qualitative approach used the netnography technique to examine the Facebook community; 1120 respondents comprising of current students and faculties from an engineering college, arts college, and 3 B-schools participated in this study. The study gathered information on users' characteristics and factors affecting purpose of using Facebook. The screening question was asked to clarify the unit of analysis in order to make sure that the respondents had only one Facebook account. Results: The findings from this study were analyzed using cluster analysis to identify groups of similar people in terms of how they responded to Facebook fundamental hooks like new referrals, games, groups&links, public networking, sharing emotions, performance sharing, information sharing, private networking, entertainment, amusement, socializing, and these results indicated the presence of three significant segments of Facebook users : Entertainers, Networkers, and Expressers. Originality/Value: This paper showed how and why people use social networking sites. The study can be used by brands and organizations to communicate effectively with customers by developing appropriate features, targeting ads, and apps to attract followers.